A novel acid-free glyoxal as a fixative for fresh histological tissues - Litmanen, Miisa (My University, 2024)
Formalin fixation and paraffin embedding (FFPE) remains the standard method for tissue processing worldwide. However, some of the tissue specimens must be dissected and examined fresh, and the use of formalin for transport and preservation is not optimal due to formalin exposure, prolonged fixation and limitation of DNA and RNA quality. Therefore, novel approaches in the pre-analytical phases of tissue handling are needed. The aim of this study was to analyse the suitability of acid-free glyoxal (GAF) as a fixative for fresh histological tissues. Specimens from a total of 10 subjects were fixed with GAF and compared to standard processed FFPE tissues. The morphology was assessed with Hematoxylin-eosin staining, antigenicity with immunohistochemistry, and quality of nucleic acids with molecular tests. Also, the preservative features of HistoCold-solution were analysed from all tissue samples by morphological and immunohistochemical assessment. The morphological quality in GAF-fixed tissues was mostly comparable, and molecular analyses showed enrichment in DNA fragment size and less RNA degradation compared to FFPE-processed samples. Nonetheless, the immunohistochemical quality remained unsatisfactory. The Tissues handled in HistoCold showed high histological and immunohistochemical quality. These results suggest the possible role of GAF in molecular pathology and HistoCold as a preservative solution for transporting fresh tissues. Because of differences in chemical structure and fixation mechanisms of glyoxal, further studies should focus on optimizing histochemical stains and processes for GAF-fixed tissues.
Keywords: fresh tissue, glyoxal, histology, molecular pathology, tissue diagnostics, tissue fixation